Battling Pornography : the American Feminist Anti-Pornography Movement, 1976-1986. - Bronstein, Carolyn (Cambridge University Press, 2011)
The rise and fall of the American feminist anti-pornography movement, discovering its origins in 1970s political and cultural conditions.